INFLUENCE OF DIVIDING COVERINGS ON QUALITY OF CASTINGS AT MOLDING OF ALUMINUM ALLOYS UNDER PRESSURE - A. A. Pivovarchik; E. A. Gorbachesvky; A. M. Mikhaltsov (Литьë и металлургия, 2014)
The results of researches on influence of separating coverings on such properties of castings as corrosion resistance, roughness of cast surface, casting density are given in article.